Studi Literatur : Analisis Efek Toksik pada Kasus Bunuh Diri Akibat Penggunaan Amfetamin - Kanza Hanun Nafisah; Liska Virgiawari Aji Rabbani; Khaila Zaharani Riyanto; Ira Amelia Putri; Jihan Al Ihsani; Dwi Larasati Setyaningrum (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the toxic effects brought about by amphetamine use and its association with suicides. Suicide is an act of ending one's own life that is often associated with mental health disorders and life pressures. Amphetamines are classified as Class II psychotropic drugs that have a strong stimulant effect on the central nervous system, causing changes in behavior and mental activity, including hallucinations, thought disorders, and emotional changes. This study was conducted based on a literature review, identifying and analyzing various suicide cases involving amphetamine use through relevant literature. The results of the literature analysis indicate that amphetamine use significantly increases the risk of suicidal behavior, which can affect neurotransmitters, potentially triggering psychosis, nerve damage, and cardiovascular issues. Chronic use leads to dependence, cognitive impairment.